Influenza surveillance in the Autonomous Province of Vojvodina, Serbia, over ten consecutive seasons (2015/16–2024/25): epidemiological trends, fatal case characteristics, and vaccination - Ristić, Mioljub; Patić, Aleksandra; Nikolić, Nataša; Kovačević, Gordana; Petrović, Vladimir (Vojnosanitetski pregled, 2025)
Background/Aim. Influenza represents a significant public health concern. The aim of this study was to analyze indicators of influenza activity over ten consecutive seasons in the Autonomous Province of Vojvodina (APV), Serbia, including age-specific and weekly distribution, and characteristics of influenza-related mortality. In addition, influenza vaccination trends in APV over the past ten seasons were assessed. Methods. A retrospective study was conducted using data from sentinel surveillance of influenza-like illness (ILI) and acute respiratory infections (ARI) among outpatients, as well as severe acute respiratory infection (SARI) and acute respiratory distress syndrome (ARDS) among hospitalized patients with fatal outcomes, along with data on the number of individuals vaccinated against influenza in APV. Laboratory confirmation of influenza-related deaths was performed at the Virology Center, Institute of Public Health of Vojvodina, Novi Sad, Serbia. Results. ILI and ARI incidence varied seasonally, peaking typically between surveillance weeks 5 and 10. The 2020/21 season showed markedly low influenza virus activity, while the 2021/22–2024/25 seasons displayed patterns typical of influenza seasons. Throughout the surveillance period, children aged 0–4 and 5–14 exhibited the highest incidence rates. Over the ten seasons, 202 laboratory-confirmed influenza-associated deaths were recorded, predominantly among men aged 24–64 years, occurring mainly during winter months. None of the patients had been vaccinated. The most common influenza A subtype was A (H1N1)pdm09 (59.4%). Fatal cases were almost evenly distributed between SARI (49.0%) and ARDS (51.0%), with ARDS being more common in adults aged 24–64 years. No statistically significant difference in the distribution of fatal outcomes was observed between the pre- and post-coronavirus disease 2019 periods (p = 0.6870). Influenza vaccination coverage among high-risk populations remained low, peaking at 17.5% among individuals ≥ 65 years in the 2020/21 season. Among healthcare workers, coverage reached over 40.0% in 2020/21 but declined to 20.0–25.0% in the subsequent seasons. Conclusion. Integrated sentinel and hospital-based surveillance encompasses monitoring of outpatient, severe, and fatal influenza cases. A significant increase in influenza vaccination coverage among high-risk groups could reduce hospitalization rates, the frequency of complications, and influenza-related deaths.
Keywords: covid-19; epidemiology; influenza, human; respiratory tract infections; serbia; vaccination; virology.